Venetoclax is a potent hepsin inhibitor that reduces the metastatic and prothrombotic phenotypes of hepsin-expressing colorectal cancer cells - Rodenas, Maria Carmen; Peñas-Martínez, Julia; Pardo-Sánchez, Irene; Zaragoza-Huesca, David; Ortega-Sabater, Carmen; Peña-García, Jorge; Espín, Salvador; Ricote, Guillermo; Montenegro, Sofía; Ayala-De La Peña, Francisco; Luengo-Gil, Ginés; Nieto, Andrés; et al. (Frontiers in Molecular Biosciences, 2023)
Hepsin is a type II transmembrane serine protease and its expression has been linked to greater tumorigenicity and worse prognosis in different tumors. Recently, our group demonstrated that high hepsin levels from primary tumor were associated with a higher risk of metastasis and thrombosis in localized colorectal cancer patients. This study aims to explore the molecular role of hepsin in colorectal cancer. Hepsin levels in plasma from resected and metastatic colorectal cancer patients were analyzed by ELISA. The effect of hepsin levels on cell migration, invasion, and proliferation, as well as on the activation of key cancer signaling pathways, was performed in vitro using colorectal cancer cells. The procoagulant function of hepsin from these cells was determined by a thrombin generation assay. A virtual screening of a database containing more than 2000 FDA-approved compounds was performed to screen hepsin inhibitors, and selected compounds were tested in vitro for their ability to suppress hepsin effects in colorectal cancer cells. Xenotransplantation assays were done in zebrafish larvae to study the effect of venetoclax on invasion promoted by hepsin. Our results showed higher plasma hepsin levels in metastatic patients, among which, hepsin was higher in those that had suffered thrombosis. Hepsin overexpression increased colorectal cancer cell invasion, Erk1/2 and STAT3 phosphorylation, and thrombin generation in plasma. In addition, we identified venetoclax as a potent hepsin inhibitor that reduced the metastatic and prothrombotic phenotypes of hepsin-expressing colorectal cancer cells. Interestingly, pretreatment with Venetoclax of cells overexpressing hepsin reduced their invasiveness in vivo. Our results demonstrate that hepsin overexpression correlates with a more aggressive and prothrombotic tumor phenotype. Likewise, they demonstrate the antitumor role of venetoclax as a hepsin inhibitor, laying the groundwork for molecular-targeted therapy for colorectal cancer.